RETRACTED: Pedagogical and psychological analysis of the works of Sadriddin Aini, the Bukhara savant - Ahmadov Olimjon; Elova Dilnoza (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001